2020
DOI: 10.1007/s40429-020-00307-x
|View full text |Cite
|
Sign up to set email alerts
|

“Who Am I” and “How Should I Be”: a Systematic Review on Self-Concept and Avatar Identification in Gaming Disorder

Abstract: Purpose of Review Gaming disorder (GD) appears to be associated with self-concept deficits and increased identification with one's avatar. The goal of this literature review is to highlight study findings assessing psychological and neurobiological correlates of self-concept-related characteristics and avatar identification in GD. Recent Findings The review was based on three literature researches on GD: (1) self-esteem, (2) emotional, social, and academic self-concept domains and avatar identification, and (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 135 publications
2
17
0
5
Order By: Relevance
“…Online gaming activities have become increasingly sophisticated in terms of the interactive experiences offered to players ( Billieux et al, 2015 , King et al, 2018 , King et al, 2019a , Lemenager et al, 2020 ). An important element of gaming that enhances this interactivity is the playable avatar projected into an immersive digital environment ( Bailey et al, 2013 , Bessière et al, 2007 , Burleigh et al, 2018 , King and Delfabbro, 2014 , Trepte and Reinecke, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Online gaming activities have become increasingly sophisticated in terms of the interactive experiences offered to players ( Billieux et al, 2015 , King et al, 2018 , King et al, 2019a , Lemenager et al, 2020 ). An important element of gaming that enhances this interactivity is the playable avatar projected into an immersive digital environment ( Bailey et al, 2013 , Bessière et al, 2007 , Burleigh et al, 2018 , King and Delfabbro, 2014 , Trepte and Reinecke, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Video games offer increasingly sophisticated interactive experiences (Billieux et al, 2015;King, Herd, & Delfabbro, 2017;King, Koster, & Billieux, 2019;Lemenager, Neissner, Sabo, Mann & Kiefer, 2020). Avatars are one of the important elements of gaming that enhances this interactivity (Gilbert et al, 2014;Sibilla & Mancini, 2018;Vasalou & Joinson, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…However, almost all types of games (e.g., sports and racing, shooters, strategy and puzzle games) can include avatars and roleplaying options (Ducheneaut, Wen, Yee, & Wadley, 2009;King & Delfabbro, 2019). Although many player-avatar interactions confer personal benefits (e.g., enjoyment, creativity, identity exploration), avatar features have recently been the focus of survey-based and neuroimaging studies into the development and maintenance of problematic gaming (Green, Delfabbro, & King, 2020;Lemenager et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A negative self-concept-defined as a high discrepancy in the evaluation between the subjective self and ideal self-is often reported to be associated with gaming and other internet related disorders [16,18,31,32]. A recent review on self-esteem and self-concept in gaming disorders, reported stable associations between gaming disorders and negative physical and academic self-concept domains [17].…”
Section: Introductionmentioning
confidence: 99%